PENGARUH BABY SPA TERHADAP PERKEMBANGAN MOTORIK PADA BAYI USIA 3-6 BULAN DI PMB FAUZIAH RITA TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI - Simanjuntak, Eva Hotmaria; Etty, Christina Roos; Siregar, Ronni Naudur (Jurnal Reproductive Health, 2022)
Almost 5-10% of preschool-aged children experience minor brain dysfunction, including impaired fine motor development. This study uses an experimental research design with descriptive. The design of this study used a one-group pre-test and post-test design without a control group. The population in this study were all infants aged 3-6 months living in the Fauziah Rita PMB service area Teluk Mengkudu, Serdang Bedagai Regency. The sample of this study was 25 people, using purposive sampling technique. The instruments in this study were a check list sheet and a KPSP sheet. Hypothesis testing using a statistical test t-dependent test. The results showed that there was an effect of baby spa on motor development at the age of 3-6 months at the midwife's clinic, Fauziah Rita, Teluk Mengkudu sub-district, Serdang Bedagai district, with a p value of 0.000 0.05. Suggestions for babies and toddlers to get baby spa services to help maintain and improve growth and development, especially at the motor development stage.